2013
DOI: 10.1111/j.1542-2011.2012.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Certified Nurse‐Midwives’ Confidence in Managing the Obstetric Care of Women with Female Genital Mutilation/Cutting

Abstract: Following the education program and the knowledge gained from it, these midwives were more confident about their ability to perform anterior episiotomy and to deliver necessary care to women with FGM/C in a culturally competent context. This education program should be expanded as more women who have experienced infibulation immigrate to the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 19 publications
(40 reference statements)
6
60
0
Order By: Relevance
“…The two studies reported on educational interventions for healthcare providers aimed at increasing caregivers’ knowledge on FGM and related health consequences [11, 12]. Details of each of these studies are provided below.…”
Section: Resultsmentioning
confidence: 99%
“…The two studies reported on educational interventions for healthcare providers aimed at increasing caregivers’ knowledge on FGM and related health consequences [11, 12]. Details of each of these studies are provided below.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 indicates the themes by paper. (Berggren, et al, 2004) 3 3 3 (Hess, 2010) 3 3 (Isman, et al, 2013) 3 3 3 (Jacoby & Smith, 2013) 3 (Korfker, et al, 2012) 3 (Lazar, et al, 2013) 3 3 (Leval, et al, 2004) 3 (Tamaddon, et al, 2006) 3 3 3 (Widmark, et al, 2002) 3 3 3 (Zaidi, et al, 2007) 3…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 papers included in the review, there were four that employed qualitative methods (Berggren et al, 2004;Isman et al, 2013;Lazar et al, 2013;Leval et al, 2004), five used a quantitative survey design (Jacoby & Smith, 2013;Korfker et al, 2012;Tamaddon et al, 2006;Widmark et al, 2002;Zaidi et al, 2007) and one used a survey design that also collected qualitative data. Eight papers were from HIC and two provided data about midwives in LMIC (Berggren, et al, 2004;Isman, et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As identified elsewhere, the inclusion of these wider facets when considering the particular situation of women is crucial for health care professionals as 'FGM is a subject that requires specific cultural expertise to facilitate communication, counselling, care and prevention' (Balfour, et al 2016, p5). Jacoby and Smith (2013), in a study concerned with testing an educational intervention, and which included a cultural broker (a women from a similar culture who had experienced FGM) further echo the centrality of cultural understanding in fostering care that is delivered in a 'compassionate and nonjudgemental manner' (p455).…”
Section: Page 9 Of 21mentioning
confidence: 99%